Synthesis of New 1H-1,2,3-Triazole Analogs in Aqueous Medium via “Click” Chemistry: A Novel Class of Potential Carbonic Anhydrase-II Inhibitors - Avula, Satya Kumar; Khan, Majid; Halim, Sobia Ahsan; Khan, Ajmal; Al-Riyami, Samia Ahmed; Csuk, Rene; Das, Biswanath; Al-Harrasi, Ahmed (Frontiers in Chemistry, 2021)
A series of novel 1H-1,2,3-triazole analogues (9a-j) were synthesized via “Click” chemistry and Suzuki-Miyaura cross coupling reaction in aqueous medium. The compounds were evaluated for their carbonic anhydrase-II enzyme inhibitory activity in vitro. The synthesis of triazole 7a was accomplished using (S)- (-) ethyl lactate as a starting material. This compound (7a) underwent Suzuki-Miyaura cross coupling reaction with different arylboronic acids in aqueous medium to afford the target molecules, 9a-j in good yields. All newly synthesized compounds were characterized by 1H NMR, 13C NMR, FT-IR, HRMS, and where applicable by 19F NMR spectroscopy (9b, 9e, 9h, 9j). The new compounds have shown moderate inhibition potential against carbonic anhydrase-II enzyme. A preliminary structure-activity relationship suggested that the presence of polar group at the 1H-1,2,3-triazole substituted phenyl ring in these derivatives (9a-j) has contributed to the overall activity of these compounds. Furthermore, via molecular docking, it was deduced that compounds exhibit inhibitory potential through direct binding with the active site residues of carbonic anhydrase-II enzyme. This study has unraveled a new series of triazole derivatives as good inhibitors against carbonic anhydrase-II.